From Divergence to Convergence: The Role of Intermediaries in Developing Competition Laws in ASEAN. (27th September 2021) - Ng, Wendy
Abstract: Despite the diversity of contexts and circumstances in which competition laws are developed and exist, many countries have enacted competition laws that are broadly similar. To learn more about the dynamics shaping the development of competition law at the national, regional, and international levels, this article investigates the development of competition law in the Association of Southeast Asian Nations (ASEAN) region, a region whose competition laws remain underexplored. This article undertakes a case study on the drafting of competition law in the ASEAN member states with the most recently drafted and/or enacted new comprehensive competition laws, that being Brunei Darussalam, Cambodia, Lao PDR, Myanmar, and the Philippines. It finds that, while there were differences in the processes of drafting and enacting competition law in these countries as well as in their local contexts, their competition laws are similar in many respects. The case study also finds that intermediaries facilitated the processes of translation and adaptation that occurred in developing competition law in these ASEAN member states. This article argues that the important role that intermediaries played in developing competition laws was a key reason for the broad convergence of these competition laws across their diverse local settings.